Women, Islam and everyday life [ renegotiating polygamy in Indonesia - Nurmila, Nina (London ; New York : Routledge, 2009)
"This book examines Islam and women's everyday life, focusing in particular on the highly controversial issue of polygamy. It discusses the competing interpretations of the Qur'anic verses that are at the heart of Muslim controversies over polygamy, with some groups believing that Islam enshrines polygamy as a male right, others seeing it as permitted but discouraged in favor of monogamy, and other groups arguing that Islam implicitly prohibits polygamy. Based on detailed fieldwork conducted in Indonesia, it provides an empirically-based account of women's lived experiences in polygamous marriages, describing the different perceptions of the practice and strategies in dealing with it. It also considers the impact of public policy, in particular Indonedia's 1974 Marriage Law which restricted the practice of polygamy. It shows, that, in fact, this law has not resulted in widespread adherence, and considers how public policy could be modified to increase its effectiveness in affecting behavior in everyday life. Overall, this book argues that polygamy has been a source of injustice towards women and children, that this is against Islamic teaching, and that a just Islamic law would need to call for the abolition of polygamy"--Publisher description.
1. Polygamy in context : family and kinship -- 2. Muslim discourses on polygamy in Indonesia -- 3. Reactions to and negotiation around polygamous marriages -- 4. Polygamous households
Description based on print version record
Includes bibliographical references (p [155]-194) and index
Keywords: Muslim women -- Indonesia -- Social conditions; Polygamy -- Indonesia; Women in Islam -- Indonesia; Muslim women; Polygamy; Women in Islam